4CPS-217 The use of cystic fibrosis conductance regulator modulators in patients with rare mutation. Issue 1 (23rd March 2023) - Monti Guarnieri, N; Fabrizzi, B; Andresciani, E; Garzone, AMF; Bagagiolo, S; Bartolucci, I; Guglielmi, S; Capone, C; Polidori, C; Pompilio, A
Abstract : Background and Importance: Cystic Fibrosis (CF) is a monogenic and multi-organ disease. This condition is related to mutations in Cystic Fibrosis Transmembrane Regulator (CFTR), the gene encoding the epithelial ion channel that normally transports chloride and bicarbonate. Therapeutic strategies deeply changed when Ivacaftor (2015) and the combination therapy Ivacaftor/Tezacaftor/Elexacaftor (ETI) (2021) were marketed. At this moment ETI therapy is licensed to treat CF's patients>6 years with at least one F508del mutation, the most common one; however, patients with rarer CFTR's mutations don't have access to this therapy. Aim and Objectives: With this work we would like to report the use of the combination therapy Ivacaftor-ETI in two young patients with rare CFTR's mutations: the N1303K/2183AA>G and the W1282X/N1303K. Material and Methods: Starting from the off-label authorisations from January-2015 to June-2022 by our Hospital Committee (composed with a Clinician, a Pharmacologist and a Hospital Pharmacyst) in accord to Law 94/98, we identified patients that required off-label CFTR modulators' combination therapy due to their CFTR's rare mutations and in vitro response to ETI therapy. For these we analysed: age at the beginning of the therapy, gender, type of mutation, clinical manifestations, period of therapy, Adverse Drug Reactions (ADRs) notified. Results: Only in 2022 two patients were authorised to use off-label CFTR modulators' combination therapy due to their rare CFTR's mutations. The first patient (P1) was a female, 20 years, W1282X/N1303K mutations; her clinical history showed meconium ileus, serious pneumopaty and she often required antibiotic therapy due to her lungs infections. The second patient (P2) was a female, 19 years, N1303K/2183AA>G mutations; her clinical history showed pancreatic and lungs insufficiency, BMI<14, infections induced by multidrug resistant Pseudomonas and Mycobacterium Abscessus, D hypovitaminosis. At first, Hospital Committee authorised 3 cycles of therapy for P1 and 4 cycles (28 days for each cycle) for P2; both of them were authorised to prolonge their therapy due to clinical evident efficacy. No significant ADRs related to treatment were notified. Conclusion and Relevance: CFTR modulators are small molecules that directly impact and achieve the function of CFTR channel. They give long-term improvements in clinical outcomes and we hope more research on their efficacy in patients with rarer CFTR's mutations. References and/or Acknowledgements: Conflict of Interest: No conflict of interest